PENGUKURAN KINERJA RUMAH SAKIT DENGAN BALANCED SCORECARD (Studi Kasus pada Rumah Sakit Umum Daerah Ngudi Waluyo Wlingi ) - Lailiyah, Shofiyatul (Jurnal Ilmiah Mahasiswa FEB, 2013)
The purpose of this study was to measure the performance of hospital "Ngudi Waluyo" Wlingi using the Balanced Scorecard concept therefore Hospital can achieve the vision and mission that has been effectively and efficiently set. The method used in this study were classified into descriptive research with a case study approach. This study shows the results in each perspective, in which perspective of the consumer on consumer satisfaction indicators show the results satisfied with the amount of 5836, the indicator shows customer retention due to poor production decreased by 7.91% from 67.89% to 59.98%,Â  while the customer Acquisition showed good results which amounted toÂ  40.02%.Â  On the financial perspectives for economic ratios showed less economical results in 2012 due to excessiveÂ  expenditures of budgeted, which is equal to 103.87%, the Efficiency RatioÂ  shows inefficient results for three consecutive years, while the ratio of effectiveness in Hospital "Ngudi Waluyo" Wlingi can be said to be effective,Â  it is proved byÂ  the achievement of budget revenues that have been made.Â  The perspective of internal business process (BOR, TOI, BTO, ALOS, GDR, NDR) is considered â€œadequateâ€. The whole of perspective of internal business processes is considered "adequate". On the learning and growth perspective on employee satisfaction indicators show the results for 2409, which means employees are satisfied, in addition to indicators of employee retention and employee productivity also showed good results. Eventually, the results ofÂ  this study indicateÂ  thatÂ  the performanceÂ  of hospitalÂ  "NgudiÂ  Waluyo"Â  WlingiÂ  whenÂ  measured using theÂ  concept ofÂ  the Balanced Scorecard entirety can be concluded "adequate". Keywords: Measuring performance, Balanced Scorecard, Hospital